(3OjhGf CHj fhGSs - (3GdMSf Hf gGfF Hf YHO GdChd Hf UHGM GdMceqj HGdhdGA, CHh fhGS , (B198 (3g` s
(3ChdgG (B:s
(3GdNeQjGJ bGd CHh fhGS Ydi bGajI GdgeRI hgj GdJj jSejgG GdfGS GdCdaqjGJ(B: (3hfOeGf jQi ZHfG Ydjg HCf jeSj hdjS Hg GfJTGA (B** (3EPG fHgJg ef fhe ScQ caGg eQI efc GdfOGA s
(3BNQgG (B:s
(3dG HCYeGdfG fWjb NdGUG jhe JHOh GdSeGJ ahb GdLHGg (B** (3ZjQ CfG Ydi GdESGAI hGdJaQjW fQLh HMSf Yah GdEdg hde fLO dg TYQG aj GdRgO Ydi bGajI GdjGA JeJ TY CHj fhGS aj GdRgO hJe HPdc LejY TYQg aj afhfg Jes
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3TgGOGJ GdQhGjI (B: s
(3GdELGRGJ h GdSeGYGJ (B:s
Keywords: (3GdCOHs